Duplications of the critical Rubinstein–Taybi deletion region on chromosome 16p13.3 cause a novel recognisable syndrome. Issue 3 (14th October 2009) - Thienpont, Bernard; Béna, Frédérique; Breckpot, Jeroen; Philip, Nicole; Menten, Björn; Van Esch, Hilde; Scalais, Emmanuel; Salamone, Jessica M; Fong, Chin-To; Kussmann, Jennifer L; Grange, Dorothy K; Gorski, Jerome L; et al.
Abstract : Background The introduction of molecular karyotyping technologies facilitated the identification of specific genetic disorders associated with imbalances of certain genomic regions. A detailed phenotypic delineation of interstitial 16p13.3 duplications is hampered by the scarcity of such patients. Objectives To delineate the phenotypic spectrum associated with interstitial 16p13.3 duplications, and perform a genotype-phenotype analysis. Results The present report describes the genotypic and phenotypic delineation of nine submicroscopic interstitial 16p13.3 duplications. The critically duplicated region encompasses a single gene, CREBBP, which is mutated or deleted in Rubinstein–Taybi syndrome. In 10 out of the 12 hitherto described probands, the duplication arose de novo. Conclusions Interstitial 16p13.3 duplications have a recognizable phenotype, characterized by normal to moderately retarded mental development, normal growth, mild arthrogryposis, frequently small and proximally implanted thumbs and characteristic facial features. Occasionally, developmental defects of the heart, genitalia, palate or the eyes are observed. The frequent de novo occurrence of 16p13.3 duplications demonstrates the reduced reproductive fitness associated with this genotype. Inheritance of the duplication from a clinically normal parent in two cases indicates that the associated phenotype is incompletely penetrant.